Proximal tubular dysfunction and kidney injury associated with tenofovir in HIV patients: a case series - Waheed, Sana (Clin Kidney J, 2015)
BACKGROUND: Tenofovir disoproxil fumarate (TDF) may cause acute kidney injury and proximal tubular dysfunction. However, no detailed studies document urinary phosphate wasting as a marker of TDF-induced tubulopathy. METHODS: Records of HIV-infected patients with presumed TDF toxicity were reviewed. We describe the characteristics and clinical course of 15 patients who had documented elevated (>20%) fractional excretion of phosphate (FEphos). RESULTS: Patients were predominantly Caucasian and male (73 and 80%, respectively), with a mean age of 56 years (range 38–76). Of the 15 patients, 11 had a estimated glomerular filtration rate (eGFR) of >90 mL/min/1.73(2) at time of TDF initiation. The mean duration of TDF therapy prior to diagnosis of TDF toxicity was 64 months. Mean FEphos was 34% (range 20–62). The mean eGFR at TDF initiation was 104 mL/min/1.73 m(2) [standard deviation (SD) 17.0] with a gradual decline to 69 mL/min/1.73 m(2) (SD 19.0) by the time of TDF discontinuation. Of 10 patients with repeated FEphos after TDF discontinuation, 9 had improvement of their FEphos. Of these individuals, 6 had normalization of their FEphos. Estimated GFR improved in 12 patients after discontinuation of TDF, though importantly, none returned to their baseline eGFR. CONCLUSIONS: Urinary phosphate wasting is a sensitive marker for TDF-induced proximal tubulopathy and is associated with unrecognized and permanent renal function decline. Tubular dysfunction can develop after years of TDF therapy in those with normal kidney function at the time of drug initiation. This suggests that continuing vigilance be maintained in all those on TDF.